DESEMPENHO FÍSICO DE POLICIAIS MILITARES: UMA ANÁLISE LONGITUDINAL POR ESPECIALIDADES/ATRIBUIÇÕES DE FUNÇÃO - LUIZ CARLOS REZENDE (2022)
Introduction. Considering the physical demands that military police officers are submitted to, tasks such as jumping, pulling, pushing, running, dragging, and lifting are fundamental for the effective exercise of this profession. The Military Police of the State of Mato Grosso do Sul is divided into units according to their specialties, requiring individual technical improvement for each kind of assignment. However, common to these units is the demand for good physical fitness. There are few studies with longitudinal analyses of the physical fitness of military police officers, especially regarding an analysis by specialties, and such knowledge is a determining feature for the development of specific training programs. Objective. Longitudinally analyze the physical fitness of military police officers according to their specialties, for a period of five years. Methods. Male military police officers were allocated into 4 groups according to assignment affinity: 1- Environmental: (Environmental Military Police - BPMA); 2- Specialized: (Special Police Operations Battalion - BOPE) and (Shock Military Police Battalion - BPChq); 3- Border: (Highway Military Police Battalion - BPMRv) and (Department of Border Operations - DOF); and 4- Urban: (1st Military Police Battalion - 1º BPM) and (Military Traffic Police Battalion - BPTran). The physical fitness test consisted of the abdominals maximum repetitions test, the barbell, and floor push-ups test, and the 12-minute run. Physical performance was analyzed retrospectively (2015 to 2019) by means of the Physical Fitness Test (PFT) results published in the Institution's Internal Bulletin. In order to compare physical test results between police specialties at baseline and over the years, an Analysis of Covariance (ANCOVA) of General Linear Mixed Model controlled for age differences between groups was performed, followed by Tukey's post hoc, respecting significance levels of (P<0.05). Results. In general, it is possible to notice a decline in the performance of the groups, with exceptions for the urban group in the running and abdominal test, and the border group in the ground push-up test. It is also observed that the specialized group performed better at baseline and that the worst results are found in the environmental group. Conclusion. There has been a decline in the physical fitness of police officers over the years and their respective work duties contribute to a further decrease or attenuation of this downgrade. Keywords: Physical Fitness; Health; Police Officers; Training Program; Militar